The Role of School Principals’ Managerial Competence in Improving Educational Performance: A Systematic Literature Review and Implications for Disadvantaged Regions - Halima, Halima; Ampa, Andi Tenri; Azis, Fatimah (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2025)
This systematic literature review synthesizes empirical findings published between 2018 and 2025 on the influence of school principals’ managerial competencies planning, organizing, directing, and controlling on educational performance in Indonesia. Using qualitative content analysis, evidence was gathered from Scopus-indexed journals, Sinta-accredited national journals, and reputable conference proceedings. The review consistently indicates that managerial competence significantly enhances teacher performance, learning quality, and student achievement, with studies reporting improvements of 25–40% through effective academic supervision, strategic planning, and resource management. Key mechanisms identified in the literature include structured instructional supervision, collaborative human-resource development, and data-driven decision-making processes that strengthen school climate and organizational efficiency. Although the review does not draw on primary data from any specific region, the synthesized evidence offers conceptual insights for disadvantaged or remote areas such as Mamuju Regency, where infrastructural limitations, resource constraints, and post-disaster vulnerabilities have been widely documented in national reports. The literature suggests that adaptive managerial strategies emphasizing supervision, planning, and climate-building may help address such contextual challenges. The review concludes that strengthening principal preparation, certification, and ongoing managerial training is essential for improving educational outcomes and reducing regional disparities. Future empirical research is recommended to examine how these competencies operate within the unique contextual realities of regions like Mamuju, thereby validating and refining the implications derived from this synthesis.